2019
DOI: 10.1016/j.tcr.2019.100248
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic spondyloptosis of L3 with incomplete neurological involvement: A case report

Abstract: High-energy traumas frequently result in lumbar spine fractures such as spondyloptosis is the maximum expression of instability and severity. The management of spondyloptosis is complex and, essentially, surgical. It usually presents with irreversible neurological compromise. This paper aimed to present a case of lumbar spondyloptosis and its early confrontation, partial neurological involvement, and progressive postoperative retrieval.Clinical caseA male patient aged 42 years had multiple injuries with asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…However, various case reports are there with different level spondyloptosis presenting with intact or remaining neurological functions. 7 20 21 22 23 24 25 26 There was 1 patient each in ASIA–C and ASIA–B and 1 patient was neurologically intact in our study cohort.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, various case reports are there with different level spondyloptosis presenting with intact or remaining neurological functions. 7 20 21 22 23 24 25 26 There was 1 patient each in ASIA–C and ASIA–B and 1 patient was neurologically intact in our study cohort.…”
Section: Discussionmentioning
confidence: 79%
“…The surgery can be done via anterior, posterior, or combined approach. 7,[20][21][22][23][24][25][26] We prefer a 4-level posterior fixation (2 levels above and 2 levels below the lesion) with pedicle screws and a rod in traumatic spondyloptosis involving thoracic, thoracolumbar, lumbar, and lumbosacral region. In patients with cervical traumatic spondyloptosis, we do anterior cervical discectomy and fusion if spinal alignment can be achieved.…”
Section: Cause Of Higher Incidence Of Spondyloptosis At This Locationmentioning
confidence: 99%
“…Most spinal fracture dislocations occur at the thoracolumbar or lumbosacral junctions 11,12 and often result in severe neurological deficits. The midlumbar location of the injury in this report is atypical and may be due to increased lateral forces at the apex of the patient's scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that neurological improvement requires surgical intervention to decompress and stabilize the spine. 4,8,11,13,14 There have been reports of successful closed reduction in spondyloptosis 12,15 and in partial lateral dislocation 16 ; however, reduction in lateraloptosis requires greater distraction forces because of the proximity of the involved vertebral bodies. 2,9 This case features several unique elements, including what the authors believe to be the first report of closed reduction for a case of lateraloptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic lumbar spondyloptosis most frequently occurs at the L4-L5 and L5-S1 levels and is associated with severe neurological deficit [ 8 ]. The injury mechanism of the patient would be compatible with the shear-type of fracture-dislocation, according to the report of Denis group [ 9 ], where all three columns were disrupted.…”
Section: Discussionmentioning
confidence: 99%